A Narrative Inquiry of Language Teacher Identity Construction in Pre-Service Teachers' Practicum Experiences - Pane, Yuneth; Tanasale, Inggrit; Que, Stella; Marasabessy, Halima (MATAI: International Journal of Language Education, 2025)
This study examined how two pre-service teachers in Ambon, constructed their teacher identities during a month-long practicum in junior and senior high schools. Using in-depth interview and photovoice (via WhatsApp), the research explored pre-service teachers’ identity development before and after the teaching practicum. Key findings revealed the practicum's significant role in shaping teacher identity, highlighting themes such as patience, classroom management, reflective practice, professional responsibility, and the challenges of teaching. The study also emphasized the importance of prior teaching experience and supportive school environment for a successful practicum. It is recommended that English department needs to build for the success of students’ teaching practicum.